THE ROLE OF EDUCATION IN PROMOTING SUSTAINABLE SOCIAL CHANGE - Utari, Reviana; Ayatullah, Ayatullah (LPPM Universitas Bina Bangsa, 2025)
This research aims to analyze the role of education as an agent of social change in the context of local and global communities, as well as identifying how educational institutions contribute to community development through various learning approaches. The research method used is a literature study with a descriptive qualitative approach, which examines various previous research results and secondary data from scientific articles, international institutional reports, and case studies in various countries, including South Africa, Portugal, England and Indonesia. The research results show that education is capable of being a catalyst for significant social change through community involvement, inclusive non-formal education, strengthening entrepreneurship in the curriculum, and responsiveness to social and technological change. This study highlights the importance of collaboration between educational institutions and communities, innovation in the curriculum, and strengthening students' social and economic competencies. Recommendations from this research emphasize the need for government, educational institutions and society to expand strategic partnerships and strengthen sustainable community-based education programs to create positive and sustainable social change.